HIV viral load suppression rates among adults and children living with HIV in the North West Region of Cameroon: A call for action! - Gladys Fosah E Tayong; Melissa Sander; Comfort Vuchas; Moses Samje; Vera Kum; Pascal Enokbonong; Eugene Yeika; Ndanga Bekombo; Paul Nyibio; Vanessa B Ngwani; Justin Ndié; Njamnshi Wepnyu Yembe; et al. (PLoS ONE)
Introduction HIV continues to be a major public health problem in Cameroon where 2.7% of the population aged 15 to 49 are living with HIV. The prevalence remains higher in females, 3.4% versus 1.9% in males. The North West region of Cameroon has a higher prevalence than the national average; 4% in the general population, 5.8% in females and 1.6% in males. Despite the availability of pediatric HIV treatment, gaps in outcomes of children living with HIV (CLHIV) persists. This study aimed to compare the HIV viral suppression rates among adults and children living with HIV receiving antiretroviral therapy (ART) in the North West Region of Cameroon. In this study we hypothesized that the virologic outcome of children living with HIV is unfavorable compared to adults. Methodology This study was a comparative cross-sectional analytical study with secondary analysis of Viral load laboratory database. Data was collected in June 2023. We systematically collected deidentified data on viral load test of all PLHIV with HIV viral load results in the Bamenda TB reference laboratory database for the period January 1, 2022 to December 31, 2022. Data was analyzed using Stata SE 14.2. Categorical variables were described using absolute and relative frequencies. These were compared using Pearson's chi-squared test. Quantitative variables were described using mean as a characteristic of central tendency and standard deviation (SD) as a characteristic of dispersion. Results Analysis revealed that of the 23,814 PLHIV whose viral load test was done at the Bamenda TB reference laboratory during the year 2022, 17,364(73%) were female and 1436 (6%) were children. The level of HIV viral suppression (viral load<1000 copies/ml) in children was lower compared to that of adults (80% vs. 95%; p<0.001). Females had lower viral suppression than males (94% vs. 91%; p<0.001). Conclusion The results revealed a significant lower HIV viral suppression rate in children than in adults. Women also had a significantly higher HIV viral suppression than males. Findings indicated that HIV viral suppression rate is significantly higher for routine viral load testing than for targeted testing after enhanced adherence counselling, thus the need to systematically offer enhanced adherence counselling and other evidence-based support interventions in routine care to all PLHIV to avoid persistent high viral non-suppression. Action is needed to tackle all known factors contributing to high viral non-suppression in children living with HIV and to help achieve 95% viral suppression rate in CLHIV in the North West region of Cameron.